THE NORMALIZATION METHODS OF THE STATIC GEOMAGNETIC FIELD INSIDE HOUSES - Rozov, V. Yu.; Zavalnyi, A. V.; Zolotov, S. M.; Gretskikh, S. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2015)
In the paper, we show the necessity of normalization of the static geomagnetic field (GMF) inside high-rise frame-monolithic houses to safe values (90% of the natural rate at least). Massive ferromagnetic construction of these buildings significantly (up to 50 %) weakens the natural GMF. The normalization methods are based on mathematical modeling of GMF in a residential area. Simplified physical models of reinforced concrete building structures are developed and used. The results of experimental studies are also used in the framework of the development of the methods. The following methods of normalization of GMF are presented and justified: 1) the use of special steel with a relative permeability less than 70 in housing construction; 2) restrictions on the use of long steel elements with the elongation coefficient in the critical range of 4<b<28; 3) demagnetization of steel reinforcement before installing; 4) preventing the magnetization of steel reinforcement in the construction process. Practical recommendations for the design of «magnetic clean» houses with comfortable living conditions in connection to the GMF are proposed.